Thrombolysis in Children: A Case Report and Review of the Literature - Woods, Gary M.; Kim, Dennis W.; Paden, Matthew L.; Viamonte, Heather K. (Frontiers in Pediatrics, 2022)
Thromboembolism (TE), including venous thromboembolism (VTE), arterial TE, arterial ischemic stroke (AIS), and myocardial infarction (MI), is considered a relatively rare complication in the pediatric population. Yet, the incidence is rising, especially in hospitalized children. The vast majority of pediatric TE occurs in the setting of at least one identifiable risk factor. Most recently, acute COVID-19 and multisystem inflammatory syndrome in children (MIS-C) have demonstrated an increased risk for TE development. The mainstay for the management pediatric TE has been anticoagulation. Thrombolytic therapy is employed more frequently in adult patients with ample data supporting its use. The data for thrombolysis in pediatric patients is more limited, but the utilization of this therapy is becoming more commonplace in tertiary care pediatric hospitals. Understanding the data on thrombolysis use in pediatric TE and the involved risks is critical before initiating one of these therapies. In this paper, we present the case of an adolescent male with acute fulminant myocarditis and cardiogenic shock likely secondary to MIS-C requiring extracorporeal life support (ECLS) who developed an extensive thrombus burden that was successfully resolved utilizing four simultaneous catheter-directed thrombolysis (CDT) infusions in addition to a review of the literature on the use of thrombolytic therapy in children.